Which aspects of health care are most valued by people living with HIV in high-income countries? A systematic review. Issue 1 (December 2016) - Cooper, V.; Clatworthy, J.; Youssef, E.; Llewellyn, C.; Miners, A.; Lagarde, M.; Sachikonye, M.; Perry, N.; Nixon, E.; Pollard, A.; Sabin, C.; Foreman, C.; et al.
Abstract Background Increasing numbers of people with HIV are living into older age and experiencing comorbidities. The development of new models of care to meet the needs of this population is now a priority. It is important that the views and preferences of patients inform the development of services in order to maintain high levels of patient satisfaction and engagement. The aim of this systematic review was to determine which aspects of healthcare are particularly valued by people living with HIV. Methods We searched electronic databases and reference lists of relevant articles. The search strategy was developed to identify articles reporting on HIV positive patients' perceptions, evaluations or experiences of healthcare services and factors associated with satisfaction with care. Peer-reviewed papers and conference abstracts were included if the study reported on aspects of health care that were valued by people living with HIV, data were collected during the era of combination therapy (from 1996 onwards), and the paper was published in English. A thematic approach to data synthesis was used. Results Twenty-three studies met the inclusion criteria. Studies used both qualitative and quantitative methods. Six studies specifically reported on relative importance to patients of different aspects of care. The valued aspects of care identified were grouped into seven themes. These highlighted the importance to patients of: a good health care professional-patient relationship, HIV specialist knowledge, continuity of care, ease of access to services, access to high quality information and support, effective co-ordination between HIV specialists and other healthcare professionals, and involvement in decisions about treatment and care. We were unable to determine the relative importance to patients of different aspects of care because of methodological differences between the studies. Conclusions This review identified several attributes of healthcare that are valued by people living with HIV, many of which would be relevant to any future reconfiguration of services to meet the needs of an ageing population. Further research is required to determine the relative importance to patients of different aspects of care.